FAKTOR-FAKTOR YANG MEMPENGARUHI LEMAHNYA EKSPOR TEH INDONESIA KE NEGARA RUSIA (2008-2012) - Marta Sari Uli Pakpahan; Idjang Tjarsono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
The position of Indonesia in international trade is one of the largest tea producers and exporters in the world . The role of tea as the raw material for the industry itself is a major contribution to foreign exchange, absorbing a large amount of labor , and the positive impact that makes tea as one of the leading commodity nationwide . Over the last 5 years , tea industry tends to decline including reduced acreage , production decline , and then also have a negative impact on the value of the volume of tea exports to Russia . The purpose of this research was to determine the factors that influence the weak of Indonesian tea exports competitiveness to Russia in 2008-2012. The author uses the theory of comparative advantage by David Richardo and the concept of competitiveness as a baseline research . The method used in this research is descriptive analytical method with a case study approach . The author obtained the data and materials based on books , journals , magazines / newspapers , theses , and websites that related to research. The final results of the research by the authors showed that the weakening of the Indonesian-Russian tea export caused by the Indonesian government policies that are less conducive to the development of a national commodity.Key Word : tea, exports, government, policies.